Exploring children's learning experience in constructionism-based coding activities through design-based research. (October 2019) - Papavlasopoulou, Sofia; Giannakos, Michail N.; Jaccheri, Letizia
Abstract: Over the last few years, the integration of coding activities for children in K-12 education has flourished. In addition, novel technological tools and programming environments have offered new opportunities and increased the need to design effective learning experiences. This paper presents a design-based research (DBR) approach conducted over two years, based on constructionism-based coding experiences for children, following the four stages of DBR. Three iterations (cycles) were designed and examined in total, with participants aged 8–17 years old, using mixed methods. Over the two years, we conducted workshops in which students used a block-based programming environment (i.e., Scratch) and collaboratively created a socially meaningful artifact (i.e., a game). The study identifies nine design principles that can help us to achieve higher engagement during the coding activity. Moreover, positive attitudes and high motivation were found to result in the better management of cognitive load. Our contribution lies in the theoretical grounding of the results in constructionism and the emerging design principles. In this way, we provide both theoretical and practical evidence of the value of constructionism-based coding activities. Highlights: Design-based research approach to investigate constructionism-based coding activities for children. Identify elements of children's engagement in constructionism-based coding activities. Theoretical grounding of the findings on constructionism theory. Instructional design principles to facilitate constructionism-based coding activities for children.